USING SUSTAINED SILENT READING STRATEGY TO IMPROVE THE NARRATIVE TEXT READING COMPREHENSION OF THE TENTH GRADERS OF SMA EL SHADAI MAGELANG IN THE SCHOOL YEAR 2018/2019 - Novi Anggraini (Faculty of Education and Teachers Training, 2020)
Reading is one of the English language skills that should be mastered by students especially for Senior High School students. The tenth graders of SMA El Shadai Magelang in the school year 2018/2019 still found difficulties in understanding the narrative text.There are two objectives of this research; the first is to know whether the use of Sustained Silent Reading Strategy can improve the learning motivation in the narrative text reading comprehension and the second is to know how great the improvement of the narrative text reading comprehension of the tenth graders of SMA El Shadai Magelang in the school year 2018/2019 is.To collect the data, the writer used non test (observation, questionnaire, and documentation) and test technique. The data was analyzed using Fowler’s formula and descriptive analysis.As the results, The mean score of the observation sheet from Pre-Cycle, Cycle I, and Cycle II were 50.71% ,71.42%, and 81.47%, while the improvement of the observation sheet was 30.75% from Pre-Cycle to Cycle II. The mean of the students’ score in Pre-Cycle were 67.5. In Cycle I the mean score was 71.42, while in Cycle II it was 85. The improvement of the students’ score from Pre-Cycle to Cycle II was 17.5 points.The writer concludes that the use of sustained silent reading strategy can improve the motivation in learning narrative text reading comprehension and there is a great improvement in narrative text reading comprehension of the tenth graders of SMA El Shadai Magelang in the school year 2018/2019.Keywords: Reading comprehension, Sustained Silent Reading strategy, Narrative Text.